Efforts to develop micro, small, and medium enterprises through education on branding, design, and financial statements - Anggi Angga Resti; Suharyati Suharyati; Mira Rahmi (Universitas Muhammadiyah Magelang, 2023)
Design and branding play a crucial role in attracting potential consumers for micro, small, and medium enterprises (MSMEs) and influencing their purchasing decisions. However, many MSME entrepreneurs still lack a clear understanding of how design and branding function, particularly as tools for product uniqueness and global market competitiveness. This program partners with Griya UKM Cinere, involving 20 MSMEs specializing in handmade crafts and fashion. The primary goal of this community service is to educate the partners about the significance of design, branding, and financial statements in boosting sales and serving as effective digital marketing tools. The program includes interactive discussions and training sessions, resulting in increased awareness among partners regarding the vital aspects of branding, design, and financial statements. Evaluation outcomes indicate that 75% of the participants have gained a solid grasp of the materials presented.